2007
DOI: 10.1111/j.1461-0248.2007.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Human impacts on the species–area relationship in reef fish assemblages

Abstract: The relationship between species richness and area is one of the oldest, most recognized patterns in ecology. Here we provide empirical evidence for strong impacts of fisheries exploitation on the slope of the species-area relationship (SAR). Using comparative field surveys of fish on protected and exploited reefs in three oceans and the Mediterranean Sea, we show that exploitation consistently depresses the slope of the SAR for both power-law and exponential models. The magnitude of change appears to be propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(58 citation statements)
references
References 46 publications
2
56
0
Order By: Relevance
“…1, Table S4); a power model was the best fit in only 10 of 57 cases. Although it has been suggested that the most appropriate model may depend on scale and the nature of the organisms or of the environment (19,22,23,43,45), no simple tendencies in these regards seem to emerge from our analyses. Indeed, all of the different shapes of SARs represented by the set of models used (convex, sigmoid, asymptotic, and nonasymptotic) were selected at least once for the different datasets.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…1, Table S4); a power model was the best fit in only 10 of 57 cases. Although it has been suggested that the most appropriate model may depend on scale and the nature of the organisms or of the environment (19,22,23,43,45), no simple tendencies in these regards seem to emerge from our analyses. Indeed, all of the different shapes of SARs represented by the set of models used (convex, sigmoid, asymptotic, and nonasymptotic) were selected at least once for the different datasets.…”
Section: Discussionmentioning
confidence: 59%
“…This suggests that none of a wide range of potential SAR models can a priori be ignored, and that a universal model does not emerge. The applied implications of this observation could be further complicated if, as some have suggested, the form of SARs can be influenced by human activities, although thus far this influence has principally been explored in terms of power models (22,46).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…comm.). As fishing pressure can affect the speciesarea relationship (Tittensor et al 2007), fish communities at Cape Leucate are most likely the result of decades of selective fishing pressure, which could explain the low densities and functional richness of the NR compared with the AR locations. For instance, Micheli & Halpern (2005) observed that due to selective fishing in temperate reefs, fishes of higher trophic levels (such as carnivores) are underrepresen ted in fished areas compared with protected areas.…”
Section: Contrasting Fish Communities Between the Ars And The Nrmentioning
confidence: 99%
“…Satellite and airborne remote sensing provide a consistent method of observation for biodiversity monitoring across space and time. It enables indirect detection of habitat quality and heterogeneity or essential environmental parameters as surrogates of forest biodiversity, and it directly describes species presence, species richness and diversity [4][5][6][7]. However, it is still difficult to identify the number of canopy species or particular species of interest in some regions with complex species distributions.…”
Section: Introductionmentioning
confidence: 99%